(untitled) (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
Ambassador Samuel Pinheiro Guimarães (1939-2024) was a diplomat of extreme courage, defending Brazil’s national dimension during the enthusiastic wave of neoliberal globalization. To do so, he dared to cross institutional and corporate boundaries. His contact with UFRGS began in 1995, when he became president of the International Relations Research Institute (IPRI), a body linked to Itamaraty. In partnership with academia, he promoted seminars, research and publications, motivating scholars who were stunned by the then dominant narrative. In 1999, it was associated with our initiative to create the Brazilian Center for Strategy and International Relations (NERINT), at the Latin American Institute for Advanced Studies (ILEA) at UFRGS. In the same year, the International Relations and Integration Collection of the UFRGS publishing house published the first edition of his emblematic work Quinhentos Anos de Periferia (Five Hundred Years of Periphery), co-edited by Contraponto, which marked Brazilian political and diplomatic thinking.